2014
DOI: 10.1162/ling_a_00148
|View full text |Cite
|
Sign up to set email alerts
|

Now I’m a Phase, Now I’m Not a Phase: On the Variability of Phases with Extraction and Ellipsis

Abstract: On the basis of a number of cases where the status of X with respect to phasehood changes depending on the syntactic context in which X occurs, I argue for a contextual approach to phasehood whereby the highest phrase in the extended projection of all lexical categories-N, P, A, and V ( passive and active)-functions as a phase. The relevant arguments concern extraction and ellipsis. I argue that ellipsis is phaseconstrained: only phases and complements of phase heads can in principle undergo ellipsis. I show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(146 citation statements)
references
References 94 publications
5
137
1
3
Order By: Relevance
“…One important property ascribed to cps in a Minimalist view of syntax is that they function as phases and also contain an internal phase -vP (Chomsky 2000), or aspp when present (Bošković 2014;Harwood 2015). Within the nominal domain, extensions of Chomsky's original proposals relating to phases in clauses have led to suggestions that dps occur as phases (Svenonius 2004;Bošković 2012; Hinzen 2012 among many others).…”
Section: Phases Within Nominal Projectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One important property ascribed to cps in a Minimalist view of syntax is that they function as phases and also contain an internal phase -vP (Chomsky 2000), or aspp when present (Bošković 2014;Harwood 2015). Within the nominal domain, extensions of Chomsky's original proposals relating to phases in clauses have led to suggestions that dps occur as phases (Svenonius 2004;Bošković 2012; Hinzen 2012 among many others).…”
Section: Phases Within Nominal Projectionsmentioning
confidence: 99%
“…More recently, in an interesting and influential series of works on this topic, Bošković (2008Bošković ( , 2009) and Bošković and Gajewski (2011) have suggested that languages which do not have (definite) articles are "np languages" and nominal constituents in such languages have no level of dp structure, and that these languages display a number of common syntactic characteristics, which may all be attributed to the absence of d/dp. The present paper approaches this debate with a focus on the potential dp status of (definite) nominal projections in Bangla, a language which has no definite or indefinite articles, but which has special word order alternations in the encoding of definiteness (shortly to be reviewed below) that have been taken to suggest a dp level of structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here too, the interpretation seems to be that the extraposed clause clarifies the exact referent of the D-like element, i. ing the notion of syntactic phases, e.g. Bošković 2014). The syntactic position of foci is crucially dependent on the position of the verb in our proposal, precluding a rigid syntactic treatment in terms of designated positions (cf.…”
Section: Hungarian Embedded Focimentioning
confidence: 99%
“…According to Chomsky (2000Chomsky ( , 2001, phase heads are transitive  and C (but see Bošković (2014) and the references cited therein for different views). When a phase is completed, the complement of the phase head is transferred to the PF and LF interfaces and is therefore no longer accessible for operations triggered by material outside the phase (the Phase Impenetrability Condition PIC; see (6) below in the text).…”
Section: Movement As Attractionmentioning
confidence: 99%